What is Needed to design sustainable and resilient cities: Neutrosophic fuzzy based DEMATEL for designing cities - Seker, Sukran; Aydin, Nezir; Tuzkaya, Umut Rifat (ELSEVIER, 2024)
Since Turkiye is in a seismically risky zone, earthquakes are common in the country and cause social and economic losses. The resilience of Turkiye to earthquakes has come to the fore again with the disaster experienced in the magnitude of 7.7 and 7.6 earthquakes that were centered in Kahramanmaras on February 6, 2023, which affected 11 provinces at once. Since resilience system planning in the cities has a real positive impact on the community for sustainability, in this study, the most contributory resiliency factors in the cities of Turkiye to earthquakes are identified and analyzed using the Neutrosophic Fuzzy DEMATEL method. As an application region, Istanbul is selected because it is anticipated to experience an earthquake in the near future, and it is the most populated city in Turkiye. The main logic of the analysis is to analyze influential relationships among factors that need to be considered to create sustainable and resilient cities and visualize the causal relationships through an influential relation map in the face of the earthquake as a natural hazard. The findings show that the diversity of economic resources, building density, economic recovery capacity, and population density are the most influential and contributory criteria to providing the sustainability and resilience of the city of Istanbul. The implications provide a new perspective for countries to enhance the earthquake resilience of towns in disaster risk management, as well as suggestions for future research.
Keywords: Neutrosophic fuzzy sets; Sustainable cities; Sustainable and resilient cities; URBAN RESILIENCE; COMMUNITY RESILIENCE; OPTIMIZATION; SELECTION; CONTEXT; RISK; Geology; Meteorology & Atmospheric Sciences; Water Resources